Analysis of posterior segment findings in acute encephalitic syndrome in a tertiary care institute - Dutta, Parmita; Deuri, Arup (International Journal of Research in Medical Sciences, 2021)
Background: Objective of the study was to determine the posterior segment findings in cases of Acute Encephalitic Syndrome(AES) in patients attending the paediatrics department of Assam Medical College. Methods: A prospective study of 36 cases of AES attending the paediatrics department of Assam Medical College during a period of 6 months was taken into consideration. Results: 36 cases of AES were studied during a period of 6 months. The maximum number of cases was around 5 years (41.6%).The number of cases in males were more than in females (63.8%vs 36.1%) .The posterior segment findings were papilledema (44.4%), optic disc hyperemia (52.7%),and retinal hemorrhages(3%). Conclusions: Analysis of posterior segment findings helps in early detection and preventing the sequalae and complications and therefore helps in saving the eye.